Mitochondria: Multifaceted regulators of aging - Son, Jyung Mean; Lee, Changhan (BMB Reports, 2019)
Aging is accompanied by a time-dependent progressivedeterioration of multiple factors of the cellular system. Thepast several decades have witnessed major leaps in ourunderstanding of the biological mechanisms of aging usingdietary, genetic, pharmacological, and physical interventions.Metabolic processes, including nutrient sensing pathways andmitochondrial function, have emerged as prominent regulatorsof aging. Mitochondria have been considered to play a keyrole largely due to their production of reactive oxygen species(ROS), resulting in DNA damage that accumulates over timeand ultimately causes cellular failure. This theory, known asthe mitochondrial free radical theory of aging (MFRTA), wasfavored by the aging field, but increasing inconsistentevidence has led to criticism and rejection of this idea.However, MFRTA should not be hastily rejected in its entiretybecause we now understand that ROS is not simply anundesired toxic metabolic byproduct, but also an importantsignaling molecule that is vital to cellular fitness. Notably,mitochondrial function, a term traditionally referred tobioenergetics and apoptosis, has since expanded considerably.It encompasses numerous other key biological processes,including the following: (i) complex metabolic processes, (ii)intracellular and endocrine signaling/communication, and (iii)immunity/inflammation. Here, we will discuss shortcomings of previous concepts regarding mitochondria in aging and their emerging roles based on recent advances. We will also discuss how the mitochondrial genome integrates with major theories on the evolution of aging.
Keywords: Aging; Animals; Apoptosis; DNA Damage; DNA, Mitochondrial; Free Radicals; Humans; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Aging; Communication; Mitochondria; Mitochondrial DNA; Signaling